How Individuals Engage in the Absorption of New External Knowledge: A Process Model of Absorptive Capacity1. Issue 3 (22nd December 2018) - Sjödin, David; Frishammar, Johan; Thorgren, Sara
Abstract : This paper offers a process model of how individuals engage in the absorption of new external knowledge. Data collection is centered on the experiences of knowledge workers in recognizing, assimilating, and applying external knowledge. The process model delineates how individuals engage in the absorptive capacity (AC) process through: (1) valuing knowledge potential by assessing the motivation to assimilate knowledge and by evaluating technological feasibility, which together constitute the recognition of value; (2) corroborating knowledge value by ensuring legitimacy and demonstrating a shared understanding of the business value in achieving knowledge assimilation; and (3) championing knowledge integration by lobbying for support and securing resources in order to integrate and apply the knowledge within the organization, ultimately ensuring that knowledge is exploited. The process model clarifies how an individual's proficiency in external knowledge absorption activities can result in three possible outcomes: knowledge is exploited, knowledge is terminated, or knowledge gets "stuck" in limbo. These findings contribute to the AC literature by underscoring the pivotal role of individual engagements in recognition, assimilation, and application of external knowledge and add new elements and a process perspective to the understanding of the path from potential to realized AC. The paper also provides insights into how individuals and firms can better manage knowledge absorption in practice.